Analysis of Soil Periods through Strong Motion Records by the Horizontal-To-Vertical Spectral Ratio Method in the District Of Chorrillos, Lima, Peru - Huamán-Binda, Carlos (2024)
This article presents the results of the analysis of predominant soil periods using the spectral ratio (HVSR) methodology, based on strong motion records at seismic stations in the Chorrillos district, Lima, Peru, a high seismicity area at the western edge of South America. The district contains fine soil deposits, different to the coarse alluvial conglomerate of Lima downtown. The seismic stations are located on sandy soils interspersed with clay strata, moderately compact to dense aeolian sands of variable thickness, and silty-clay soils followed by peat with intercalations of silty sand, according to the existing seismic microzonation. The results indicate that the HVSR method can be very useful to determine the predominant soil periods, which represent the soil profile on which the strong motion record has been recorded. These soil periods, which are in the range of 0.21 s to 0.49 s, are compared with those determined from previous microtremor measurements and inferred from geophysical tests of shear wave velocity, obtaining a good correlation. Also, site classification of the soil profile at these stations is verified according to the Peruvian Seismic Code.